1992
DOI: 10.1104/pp.99.2.468
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Environment Effects on Rapeseed Microspore Development and Culture

Abstract: The influence of donor plant growth conditions on microspore embryogenesis in rapeseed (Brassica napus) was metric measurements of the microspores isolated from 2.5-to 5.0-millimeter buds showed that the microspores isolated from low-temperature-grown plants had significantly lower log 90-degree light scatter to forward angle light scatter and log 90-degree light scatter to time of flight ratios than those isolated from high-temperature-grown plants, suggesting that the former are more translucent than the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…The most important element of the DH technology allowing an increase in the yield of regenerated plants is the increased induction of microspore embryogenesis. Some parameters of DH technology (growing donor plants at low tempe ratures, heat treatment of microspores during the first days of cultivation (Lo and Pauls, 1992;Cegielska Taras et al, 2002), and the use of media with a high sucrose content (Baillie et al, 1992;Ilic Grubor et al, 1998;Ferrie et al, 1999;Lionneton et al, 2001) are universal for the Brassica genus. According to pub lished data, the efficiency of embryogenesis depends on factors such as the plant genotype, the develop mental stage of microspores, the type of pretreatment of buds and microspores, the composition of culture media, and culture conditions (Ferrie et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The most important element of the DH technology allowing an increase in the yield of regenerated plants is the increased induction of microspore embryogenesis. Some parameters of DH technology (growing donor plants at low tempe ratures, heat treatment of microspores during the first days of cultivation (Lo and Pauls, 1992;Cegielska Taras et al, 2002), and the use of media with a high sucrose content (Baillie et al, 1992;Ilic Grubor et al, 1998;Ferrie et al, 1999;Lionneton et al, 2001) are universal for the Brassica genus. According to pub lished data, the efficiency of embryogenesis depends on factors such as the plant genotype, the develop mental stage of microspores, the type of pretreatment of buds and microspores, the composition of culture media, and culture conditions (Ferrie et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures probably vary endogenous levels of anther hormones and metabolites and could modify the frequency of symmetric cell division and control the characteristics of microspore (Lo and Pauls, 1992;Custers et al, 1994). High culture temperature is a key factor for the transition from gametophytic to sporophytic development of microspores by promotion of the vegetative nucleus in binucleate pollen (Custers et al, 1994).…”
Section: Integration Of New Biotechnologies In Breeding Programsmentioning
confidence: 99%
“…Microspores are generally embryogenic at the uninucleate stage (Kott et al 1990;Telmer et al 1992;Kott 1998), but those at an early binucleate stage are still able to change their developmental program from pollen maturation to the embryogenic pathway (Pechan and Keller 1988;Huang et al 1990). In this case a different cytological development is observed (Kott et al 1988;Zaki and Dickinson 1990;Lo and Pauls 1992;Telmer et al 1993), for example, an abundance of starch grains has been described (Telmer et al 1993). However, morphological differences between embryogenic and non-embryogenic microspores have also been observed (Zaki and Dickinson 1991;Nitta et al 1997).…”
Section: Factors Influencing Embryo Yieldmentioning
confidence: 80%
“…Moreover, the development of these embryos was also better as cotyledons developed separately, in contrast to microspore-derived embryos from the other temperature variants where cotyledons were fused. The donor plant also influences microspore embryogenesis: In rapeseed (B. napus) this influence has been studied by Lo and Pauls (1992). They demonstrated that significantly higher embryo yields were obtained in microspore cultures initiated from donor plants grown at 15/12°C instead of 23/18°C in a light/dark cycle of 16/8 h.…”
Section: Other Factorsmentioning
confidence: 98%
See 1 more Smart Citation